Clinical outcomes for Day 3 double cleavage-stage embryo transfers versus Day 5 or 6 single blastocyst transfer in frozen–thawed cycles: a retrospective comparative analysis. Issue 12 (December 2021) - Rao, Jinpeng; Qiu, Feng; Tian, Shen; Yu, Ya; Zhang, Ying; Gu, Zheng; Cai, Yiting; Jin, Fan; Jin, Min
Objective: This study aimed to compare the clinical outcomes for transfer of Day 3 (D3) double cleavage-stage embryos and Day 5/6 (D5/6) single blastocysts in the frozen embryo transfer (FET) cycle to formulate a more appropriate embryo transplantation strategy. Methods: We retrospectively analyzed 609 FET cycles from 518 women from April 2017 to March 2021. All FETs were assigned to the D3-DET group (transfer of a Day 3 double cleavage-stage embryo), D5-SBT group (transfer of a Day 5 single blastocyst), or D6-SBT group (transfer of a Day 6 single blastocyst). Clinical outcomes were comparatively analyzed. Results: There were no significant differences in the biochemical pregnancy rate, clinical pregnancy rate, or ongoing pregnancy rate between the D3-DET and D5-SBT groups, but these rates in the two groups were all significantly higher compared with those in the D6-SBT group. The implantation rate in the D5-SBT group was significantly higher than that in the D3-DET group. The twin pregnancy rate in the D5-SBT and D6-SBT groups was significantly lower than that in the D3-DET group. Conclusion: This study suggests that D5-SBT is the preferred option for transplantation. D6-SBT reduces the pregnancy rate, making it a more cautious choice for transfer of such embryos.